Identification and characterization of the enzymes responsible for the metabolism of the non‐steroidal anti‐inflammatory drugs, flunixin meglumine and phenylbutazone, in horses. Issue 1 (5th August 2020) - Knych, Heather K.; Finno, Carrie J.; Baden, Russell; Arthur, Rick M.; McKemie, Daniel S.
Abstract: The in vivo metabolism and pharmacokinetics of flunixin meglumine and phenylbutazone have been extensively characterized; however, there are no published reports describing the in vitro metabolism, specifically the enzymes responsible for the biotransformation of these compounds in horses. Due to their widespread use and, therefore, increased potential for drug–drug interactions and widespread differences in drug disposition, this study aims to build on the limited current knowledge regarding P450‐mediated metabolism in horses. Drugs were incubated with equine liver microsomes and a panel of recombinant equine P450s. Incubation of phenylbutazone in microsomes generated oxyphenbutazone and gamma‐hydroxy phenylbutazone. Microsomal incubations with flunixin meglumine generated 5‐OH flunixin, with a kinetic profile suggestive of substrate inhibition. In recombinant P450 assays, equine CYP3A97 was the only enzyme capable of generating oxyphenbutazone while several members of the equine CYP3A family and CYP1A1 were capable of catalyzing the biotransformation of flunixin to 5‐OH flunixin. Flunixin meglumine metabolism by CYP1A1 and CYP3A93 showed a profile characteristic of biphasic kinetics, suggesting two substrate binding sites. The current study identifies specific enzymes responsible for the metabolism of two NSAIDs in horses and provides the basis for future study of drug–drug interactions and identification of reasons for varying pharmacokinetics between horses.